Toponomy of Village Names at Namo Rambe Sub-district: An Anthropolinguistic Study - Sinaga, Lara Desma; Lubis, Tasnim (TALENTA Publisher, 2023)
The naming system is a fascinating study because it is not only related to linguistics but also to the culture that lives in a society, likewise, with the naming of villages in the Namo Rambe sub-district. The problem in this study is how the toponomy of village names in the Namo Rambe sub-district uses anthropolinguistic study. This research aims to find the toponymy of village names in the Namo Rambe sub-district. The theory used is the theory of toponymy and anthropolinguistics. The method used is qualitative, with professional recording and note-taking techniques and literature study methods. From the results of the study, it was found that six villages were using the word Namo, one village with the word lau, one village with the word mountain, four villages with elements of flora and fauna, one village with the word house, two villages related to Hope and the naming of the village with seven standing processes. The naming system for Namo Rambe Sub-district villages shows cultural values still preserved in this community.